Analysis of photographs to view the educational situation through new lenses: An experience with medical student assistants (Itinerarios Educativos, 2024)
Observation stands out as a key strategy for teacher training, allowing for the fostering of a critical and pondering view of the educational situation. This paper describes a teacher training proposal implemented at the Faculty of Medical Sciences of the National University of La Plata, focused on pondering on university teaching through the observation and analysis of photographs. The Pedagogical Department of this Faculty designed and carried out a pedagogical module aimed at Medical Student Assistants. This module included both in–person and distance activities, where images of educational situations were analyzed using some concepts from educator Paulo Freire as a reference. The experience provided an opportunity for the student assistants to view the teaching scene through new lenses, in light of contributions from the educational sciences and to begin a process of reviewing their teaching practices.
Keywords: teacher training; student assistant; medical training; observation